KELAYAKAN FILM DOKUMENTER SUBMATERI PEMANFAATAN KEANEKARAGAMAN HAYATI KELAS X SMA - Florensia Maylandara; Syamswisna Syamswisna; Reni Marlina (Universitas Tanjungpura, 2022)
This research aimed to determine the feasibility of documentary film media as a medium of learning in the delivery of submaterial on the utilization of Indonesian biodiversity class X compiled based on the results of plant exploration as a ritualistic Dayak Kanayatn in the Paloan Village, Landak District. The research method used is descriptive with a qualitative research form. The sampling technique used purposive sampling. Five validators were tested for documentary film media. The validators consisted of two lecturers at the Biology Education Study Program, FKIP Untan, one biology teacher at Santo Benediktus Pahauman High School, one biology teacher at SMA Negeri 2 Sengah Temila, and one biology teacher at Harapan Pahauman High School. Based on the research, it was found that the CVI value was 0.99, so that it was declared feasible to be used as a learning media for learning media.